Wealth-to-Income Ratio and Stock Market Movements: Evidence from a Nonparametric Causality Test - Balcilar, Mehmet; Gupta, Rangan; Sousa, Ricardo M.; Wohar, Mark E. (Wiley, 2018)
We use a nonparametric causality-in-quantile test to analyze the predictive ability of the wealth-to-income ratio (sty) for excess stock returns and their volatility. Our results reveal that the wy is nonlinearly related with excess stock returns, and hence, results from linear Granger causality tests cannot be deemed robust. When we apply the nonparametric causality-in-quantile test, we find that the wy can predict excess stock returns over the majority of the conditional distribution, with the exception being the extreme ends, that is, when the market is in deep bear or bull phases. However, the wy has no predictability for the volatility of excess stock returns.
Keywords: Cointegration; Consumption